Use of Similar Trademarks According to Law Number 20 of 2016 Concerning Trademarks and Geographical Indications (Case Study of Supreme Court Decision Number 162K/Pdt.Sus-HKI/2021) - Ivana Trixie; Urbaniasi Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
In this modern era, people's creativity is growing rapidly, this has led to the birth of innovative products. To be able to distinguish these products are usually called trademarks. The research method used is juridical-normative and literature approach. Trademarks are the essence of the smooth trading of goods or services. In accordance with the trademark system in Indonesia according to the National Legal Development Agency (BPHN), namely the first to file principle system, meaning that the owner of a trademark license registers his trademark with the Director General of Intellectual Property Rights first. Regulations regarding these trademarks are stipulated by the Indonesian government with the aim of avoiding similarities between products in circulation. However, there are still many disputes regarding similar trademarks, and settlement of trademark disputes can be carried out if the licensee files a lawsuit against the Commercial Court. Another alternative in dispute resolution is arbitration.